The Impact of the War in Ukraine on the Indigenous Small-numbered Peoples’ Rights in Russia - Ekaterina Zmyvalova (Arctic Review on Law and Politics, 2022)
This article discusses how the war in Ukraine, started by Russia, impacts the lives of Russian Indigenous small-numbered peoples. First, one can observe Russia’s growing disregard for its international legal obligations. Second, the Russian State is continuously introducing new sanctions against persons and organizations who do not support the Russian regime. Third, the pressure on Indigenous peoples’ representatives is increasing. Fourth, a significant number of members of Indigenous small-numbered peoples actively participate in the war due to, inter alia, socio-economic problems and lack of reliable and objective information about it. Fifth, there is a decline in international cooperation with the Indigenous small-numbered peoples of Russia. Finally, it is visible that the role of Indigenous peoples, including Russian Indigenous peoples, in international decision-making changes.